Pendampingan Kegiatan Pengajaran CALISTUNG (Membaca, Menulis, Menghitung) Pada Kejar Paket A di PKBM Budi Luhur Kabupaten Tangerang - Evelin, Fanesa; Siregar, Herlina; Fauzi, Ahmad (Assoeltan: Indonesian Journal of Community Research and Engagement, 2024)
Package A Chase at PKBM Budi Luhur Tangerang Regency is a form of non-formal education that is equivalent to basic education, aimed at helping children or adolescents who cannot complete formal education. The CALISTUNG teaching program (reading, writing, counting) is a basic skill that is very important to teach to children. However, there are a number of children at PKBM Budi Luhur who have difficulty in mastering this skill, so this community service aims to provide a fun and easy-to-understand teaching approach. The method used is Community-Based Research (CBR), which involves students, teachers, and schools in designing and implementing training. Students are directly involved in the journalistic process, from data collection to news publication, with guidance and feedback from experts. Evaluation is carried out through observation and assessment of student work results, as well as interviews to assess changes in children or adolescents who cannot complete formal education. The results of this activity show an increase in CALISTUNG skills in children, especially in terms of vocabulary and reading skills. Fun teaching also motivates students to be more active in learning and participating in the Package A program. In conclusion, a varied and systematic approach in teaching CALISTUNG at PKBM Budi Luhur has succeeded in supporting a more effective learning process, helping children achieve the basic competencies needed to continue formal education.